2000
DOI: 10.1590/s0074-02762000000300012
|View full text |Cite
|
Sign up to set email alerts
|

Biological screening of Brazilian medicinal plants

Abstract: In this study, we screened sixty medicinal plant species from the Brazilian savanna ("cerrado")

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
195
0
48

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 346 publications
(246 citation statements)
references
References 10 publications
(10 reference statements)
3
195
0
48
Order By: Relevance
“…Alves et al (2000) showed a discrete antifungal activity against Cladosporium sphaerospermum (a filamentous fungus not tested in our work) for methanol extract of the leaves of L. pacari in agar diffusion assay. The dichloromethane, ethyl acetate and ethanol extracts of the stem bark of Bowdichia virgilioides showed a selective antifungal activity towards hyalohyphomycetes and dermatophytes (MICs = 100-1000 µg/mL), but had no action against yeasts.…”
Section: Seven Medicinal Plants (Bowdichia Virgilioides Calophyllum mentioning
confidence: 70%
See 1 more Smart Citation
“…Alves et al (2000) showed a discrete antifungal activity against Cladosporium sphaerospermum (a filamentous fungus not tested in our work) for methanol extract of the leaves of L. pacari in agar diffusion assay. The dichloromethane, ethyl acetate and ethanol extracts of the stem bark of Bowdichia virgilioides showed a selective antifungal activity towards hyalohyphomycetes and dermatophytes (MICs = 100-1000 µg/mL), but had no action against yeasts.…”
Section: Seven Medicinal Plants (Bowdichia Virgilioides Calophyllum mentioning
confidence: 70%
“…The other 13 plant extracts showed no antibacterial activity (Table 2), in spite of some works support of antibacterial activity against gram-positive bacteria by leaves (Alves et al, 2000) and leaves and stem bark extracts of L. pacari and B. virgilioides (Alves et al, 2000) as well as bark extract of S. obovatum (Sanches et al, 2005). Such discrepant results may be related with some factors, in particular to environmental factors (seasonality, temperature, collect local, soil nutrients, etc.…”
Section: Seven Medicinal Plants (Bowdichia Virgilioides Calophyllum mentioning
confidence: 94%
“…In the last years, C. sylvestris has been exploited in the development of creams against herpes and commercialized in mixed formulations with other plants to Duke and Vásquez (1994) prepare teas and infusions with therapeutical purposes (Camargo et al 1993, Alves 2000, Simões et al 1999). An infusion can be easily obtained (20 g of dried leaves per 1 L of water) for oral consumption (2-3 times/day) together with meals, in case of gastric ulcers or for topical treatment of wounds, burns, rashes, eczema and vitiligo (Blanco 2010).…”
Section: Pharmacological Propertiesmentioning
confidence: 99%
“…The majority of these studies focus on its active principle, normally organic compounds with diverse functions in the body. Given that their consume is increasing, it is interesting to use these plants as a supplement in food taking into account that these plants can present a significant amount of copper, iron, and zinc (ALVES, 2000;CORREA, 1984;TAKASE, 2005a, b).…”
mentioning
confidence: 99%